Simple Promethazine Method for Direct Spectrophotometry Determination of Nitrite in Water - Xu, Juncui; Bi, Jian-Hong; Wang, Xiaobo; Wang, Yubiao (Asian Journal of Chemistry, 2010)
A rapid, simple and most economical spectrophotometric method was proposed for the determination of nitrite in water sample. The method is based on coloured complex formation between nitrite and promethazine in acidic medium. The colourization of the complex by nitrite was exploited to monitor the reaction spectrophotometrically at 249 nm. The method was optimized for effect of concentrations of promethazine, various acids, concentrations of sulphuric acid, order of reagents addition and colour stability. The colour of the complex was found to be stable for ca. 2 d. The linearity range of the calibration graph was over 7.00-70.00 μg mL-1 of nitrite. The method has been applied for the determination of trace nitrite in lake water with satisfactory results.